Conceptual Maps Applied to Remote/Virtual Laboratories for Active Learning - Rafael, Silviano (2022)
The active construction of knowledge in a laboratory environment requires the application of a set of pedagogical techniques in order to avoid rote learning in engineering education. This paper presents the implementation of conceptual maps in laboratory context of an engineering course unit as an active pedagogical approach to foster the students’ meaningful learning in times of COVID pandemic. Different methodologies of laboratory work are first pre- sented, as well as the meaning of conceptual map. Then, an application example on how the conceptual map was introduced in a first laboratory class of Elec- trical Engineering, and also the students’ experiences and difficulties encoun- tered when dealing with the practical implementation of conceptual maps, is illustrated. Finally, some relevant conclusions about the implementation of this active pedagogical approach are given, in particular the development of the students’ meaningful learning by exploring relationships between concepts, ideas or propositions, by addressing the most important differences and by revealing inconsistencies on the topics studied.